Primary versus secondary head injuries - the importance in forensic pathology practice: a case report - Chng, Kay Ly; Mohd Mussadik, Umul Khairil Fatimah; Zaki, Hafizatul Solehah; Hasim, Husna Syaza; Zainun, Khairul Anuar (Academy of Medicine of Malaysia (AMM), 2025)
Introduction: Cases of traumatic brain injury (TBI) with periods of survival are not uncommon in forensic pathology practice. Autopsy in this cohort plays a crucial role as it provides vast information from multiple points of view. Case report: The deceased, an adult male, was allegedly hit on the head during an altercation, succumbed to death after being treated conservatively for one and a half days. He had sustained primary and secondary head injuries. The primary head injuries had led to increased intracranial pressure, hence causing herniation and subsequently post-traumatic cerebral infarction. No significant natural disease contributed to death. Discussion: Differentiating primary from secondary injuries is very crucial in coming into best expert opinion for cases of TBI with period of survival. It is of paramount importance to extricate this information as not to mistake these secondary changes as contusions, as it will imply that the number of impacts and overall, the mechanisms are different.